Produção de biogás por meio de biodigestão anaeróbia da vinhaça com enriquecimento nutricional - Morell, Pedro Oswaldo (2015)
This work showed the use of vinasse derived from the distillation of alcoholic fermentation of sugarcane juice, to evaluate the methanogenic potential. Through the use of fractional factorial design, reactors tests were performed in laboratory scale, assessing the vinasse variables, urea, phosphate monobasic potassium and dibasic potassium phosphate, the inoculum used, was the effluent of swine termination. The tests were conducted in a water incubator at 35 oC with hydraulic retention time of 14 days, and evaluated the volume of biogas produced in the period in which, by means of statistical evaluation of the results obtained, we selected variables for optimization of biogas production. The optimization was carried out through the use of Central Rotational Composite Designs (CRCD), using the variables vinasse and urea, in which reactors tests were performed in laboratory scale, which were conducted in a water incubator at 35 oC with hydraulic retention time of 14 days, being evaluated the volume of biogas and the concentration of methane produced.Verifying the optimization of biogas production with increasing proportion of urea in different combinations.